MENELAAH POTENSI RISIKO FINANSIAL DI KALANGAN EKSPORTIR KOPI SUMATERA UTARA - Sriwardany, Sriwardany; Fadhilah, Dita Deviana; Sunny, Rainal (Jurnal Daya Saing, 2024)
Data and information about coffee in Indonesia show optimism for the growth of coffee agribusiness. Sumatra Utara is one of the regions that plays a role in its growth. Coffee exporters in Sumatra Utara are the spearhead of Sumatra Utara’s coffee commodities and its surroundings in penetrating the international market. However, in practice, exporters also face financial risks. This study is intended to examine the financial risks of coffee export activities in Sumatra Utara. By processing the data and information that we obtained using the calculation of the Risk Score Value and Risk Priority Number, we present the priority financial risks in this paper. We found that of the 30 coffee exporters who were our respondents, the transaction system they used to export coffee was non-Letter of Credit. They are also aware of how different the risks and costs of the system are compared to Letter of Credit. Through the processing of primary data collected in the field, we obtain seven financial risks in coffee export activities in North Sumatra. The three priority risks with the highest Risk Priority Number are the risk of broken promises, the risk of a fall in the value of the dollar and changes in importing country regulations. However, among the seven risks, only broken promises have the highest scores in the Risk Score Value and Risk Priority Number calculations. We also describe efforts that can be made in managing these risks.